Modern metropolis and daily practices within spaces of encounter: metrobuses of Istanbul - Cihan, Özlem (İstanbul Bilgi Üniversitesi, 2023)
ABSTRACT: Modern individuals live with the city. Nowadays, the content of this experience is significantly realized in metropolitan areas. Inhabitants practice in the spatially and temporally regulated, organized, and appropriated structure of the metropolis. An individual's practice as an inhabitant and then as an urban citizen is constructed through a city-appropriated essence. With its vast areal scale and planning paradigm of neoliberal governmentality, the metropolis enframes inhabitants' private but also public practices in its spatial structure that corresponds to market principles. Consequently, metropolitan inhabitants growingly become subjects of a homogenous consumption that prevailed in the spatial structuring of life practices. As they become more consumers than producers in the city, they are growingly losing their ability to relate and belong. Hence, the essence of togetherness is significantly actualized through the daily routines of embodied spaces for diverse and distant inhabitants of the metropolis. As a notable example of the condition, Istanbul’s metropolitan growth comes to the fore. Following the developmental planning paradigm, Istanbul has become one of the biggest metropolises in the world by eventually introducing its famous transportation system to meet growing demands for spatial-temporal maximization of mobility, the metrobus. In this light, the dissertation aims to analyze the idea and practice of togetherness realized in everyday practices of encountering spaces in Istanbul. The metrobus, as an important space for the plural and diverse encounters, has been selected as the subject of inquiry. Through field research conducted with semi-structured in-depth interviews between 2019 and 2020, the dissertation will present Istanbul’s spatial essence in the constitution of everyday life practices and the socio-spatial characteristics of transit mobility for regular metrobus passengers. The entangled layers of ordinary practices and regular transit mobility in Istanbul to make sense of socio-spatial togetherness will be questioned through encounters and interlocutors’ perceptions of being with others, hence togetherness.

ÖZET: Modern bireyler şehirle birlikte yaşarlar. Günümüzde bu deneyimin içeriği büyük ölçüde metropollerde gerçekleşmektedir. Sakinleri, metropolün mekansal ve zamansal olarak düzenlenmiş, organize edilmiş ve sahiplenilmiş yapısında pratikler gerçekleştirir. Kamusal pratikler, aynı şekilde, metropolün geniş ölçeğinde yeniden yapılandırılır. Bireyin bir sakin olarak ve ardından bir kent vatandaşı olarak pratiği, kentin ona mal ettiği bir öz aracılığıyla inşa edilir. Geniş ölçeği ve neoliberal yönetimselliğin planlama paradigması ile metropol, piyasa ilkelerine tekabül eden özgün mekansal yapısı içinde yaşayanların özel ve aynı zamanda kamusal pratiklerini çerçeveler. Sonuç olarak, metropol sakinleri, gündelik yaşam pratiklerinin mekânsal yapılanmasında egemen olan homojen tüketimin özneleri haline gelmektedir. Şehirde üreticiden çok tüketici haline geldikçe, ilişki kurma ve ait olma yeteneklerini de giderek daha fazla kaybederler. Dolayısıyla, birlikteliğin özü, metropolün farklı ve uzak sakinleri için somutlaştırılmış alanların günlük rutinleri aracılığıyla önemli ölçüde gerçekleşir. Bu durumun önemli bir örneği olarak İstanbul'un metropoliten büyümesi ön plana çıkıyor. 1980'lerden sonra süreklilik içinde hüküm süren planlama paradigması ile dünyanın en büyük metropollerinden biri haline gelen İstanbul, hareketliliğin mekansal-zamansal maksimize edilmesine yönelik artan talepleri karşılamak için ünlü ulaşım sistemini yani metrobüsü kullanıma sundu. Bu bağlamda, çalışmanın amacı, İstanbul'daki karşılaşma mekanlarının gündelik pratiklerinde gerçekleştirilen birliktelik fikri ve pratiğini analiz etmektir. Çoğul ve çeşitli karşılaşmalar için önemli bir mekân olan metrobüs, araştırmanın saha çalışması olarak seçilmiştir. Tez, 2019-2020 yılları arasında yarı yapılandırılmış derinlemesine görüşmelerle gerçekleştirilen saha araştırması yoluyla, İstanbul'un gündelik yaşam pratiklerinin oluşumundaki mekansal özünü ve düzenli metrobüs yolcuları için toplu taşıma hareketliliğinin sosyo-mekansal özelliklerini ortaya koyacaktır. Sosyo-mekansal birlikteliği anlamlandırmak için İstanbul'daki sıradan pratiklerin ve düzenli toplu taşıma hareketliliğinin iç içe geçmiş katmanları, karşılaşmalar ve muhatapların başkalarıyla birlikte olma, dolayısıyla birliktelik algıları üzerinden sorgulanacaktır.
Modern metropol ve karşılaşma mekanlarında gündelik pratikler: İstanbul’un metrobüsleri
Keywords: İstanbul; Toplumsal Mekân; Gündelik Yaşam; Metrobüs; Biraradalık; Istanbul; Social Space; Everyday Life; The metrobus; Togetherness